Systems analysis and design - Dennis, Alan; Roth, Roberta M. [ (Roberta Marie)] , 1955-; Wixom, Barbara Haley , 1969- (Hoboken, New Jersey : Wiley, 2015)
"The 6th Edition of Systems Analysis and Design continues to offer a hands-on approach to SAD while focusing on the core set of skills that all analysts must possess. Building on their experience as professional systems analysts and award-winning teachers, authors Dennis, Wixom, and Roth capture the experience of developing and analyzing systems in a way that students can understand and apply. With Systems Analysis and Design, 6th Edition, students will leave the course with experience that is a rich foundation for further work as a systems analyst"
1. The system analyst and information systems development -- 2. Project selection and management -- 3. Requirements determination -- 4. Use case analysis -- 5. Process modeling -- 6. Data modeling -- 7. Moving into design -- 8. Architecture design -- 9. User interface design -- 10. Program design -- 11. Data storage design -- 12. Moving into implementation -- 13. Transition to the new system -- 14. The movement to objects (online only)
Includes index
Keywords: Computer architecture; System analysis; System design